A Study of Clinical Presentation and Etiology of Ring Enhancing Lesions in CT Scan Brain in Children - Prudhivi Srinivas; K. Muralidhar Reddy (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
Background: The ring enhancing lesion identification and characterization was entirely in the post CT era. The ring enhancing lesion could not be seen on angiograms, pneumo encephalograms (or) ventriculograms. The introduction of computerized tomography in India in early 1980’s demonstrated that several patients presenting with seizures had ring enhancing lesions in brain. The aetiological diagnosis of ring enhancing lesions lies in the pathological examination of excised lesions. However it is not easy to accomplish for several valid reasons. In the post CT era various presumptive diagnoses such as tuberculoma, cysticercosis, transient viral encephalitis, microabscesses, postictal enhancement and vascular lesions were considered. Subjects and Methods: This study was conducted in Department of Pediatrics, Narayana Medical College. This study was done over a period of 1 year. A total of fifty cases were taken up for this study. For the diagnosis of NCC “Diagnostic criteria and degrees of diagnostic certainty for human cysticercosis” proposed by Del Brutto et al was followed. Those patients who met the criteria of “Definitive diagnosis” were diagnosed as NCC. Those patients who were satisfying the criteria of “possible or probable diagnosis” and in the absence of criteria for the diagnosis of Tuberculoma were considered as undetermined group, because diagnosis was not confirmative in these groups of patients. Results: Of 50 cases studied 32 cases were definitive NCC and 13 cases met the criteria of probable NCC, so kept in undetermined group. Of the 32 children with NCC 94% patients presented with seizures with or without associated features. About 6% patients presented without seizures. Among non-seizure manifestations focal and raised ICT were equal. Of the 5 cases of Tuberculoma 3(60%) presented with seizures alone. 20% cases presented with seizures with raised ICT and 20% presented with seizures with raised ICT and focal deficit. Commonest clinical presentation of Tuberculoma was seizures with or without associated features. Conclusion: The most common presentation of children with ring enhancing lesion in CT scan brain are seizures (76%). Seizures with focal deficit and features of raised ICT constitutes (18%), only raised ICT and focal deficit (6%). So, ring enhancing lesion should be considered in those who presented with these symptoms in endemic areas like India. Among the seizures 70.21% are partial seizures, 8.51% are secondary GTCS, 21.28% are primary GTCS.